Performansi Alat Pengering Terowongan Tenaga Surya Tipe Hohenheim untuk Pengeringan Kerupuk Tiram - Rita Khathir; Eka Pratika Sari; Raida Agustina (agriTECH, 2020)
The aim of this study is to evaluate the performance of type Hohenheim solar tunnel dryer in drying Oyster kerupuk. This dryer was designed based on solar energy under two systems i.e. by using a solar collector and a greenhouse effect. The dryer has a dimension of 2 m length and 1m width, with about 1.5 m² and 0.5 m² drying and absorber area, respectively. In addition, oyster kerupuk were dried at 3 different depth layers, including at 2, 4, and 6 mm, and the parameters observed comprise solar irradiation, temperature and humidity, moisture and the protein content of oyster kerupuk. The results showed an average solar irradiation of 370-390 W/m², with potential application between 9.00 am-17.00 pm, daily. Moreover, the temperature at the drying chamber was gained within the range 39.7-40.9 °C, while the average ambient temperature was 31.3-3.6 °C. The drying chamber had a relative humidity of 47.8-50.5%, and was reportedly lower than the ambient value. Furthermore, the drying time used at a 2 mm layer depth was 10 h, while 12 hours was required for the 4 and 6 mm. The moisture content of samples at 2, 4, and 6 mm was 6.5%, 10.08 and 9.68%, respectively, while the protein composition was 6.52%, 7.62%, and 8.89%, correspondingly. Hence, the Hohenheim tunnel dryer is estimated to possess adaptive characteristics required for the drying process of oyster kerupuk at the 6 mm depth, although further evaluation is needed to improve its performance.